Moving to the Rhythm with Clock (Circadian) Genes, Autophagy, mTOR, and SIRT1 in Degenerative Disease and Cancer - Maiese, Kenneth (Current neurovascular research, 2017)
The mammalian circadian clock and its associated clock genes are increasingly been recognized as critical components for a number of physiological and disease processes that extend beyond hormone release, thermal regulation, and sleep-wake cycles. New evidence suggests that clinical behavior disruptions that involve prolonged shift work and even space travel may negatively impact circadian rhythm and lead to multi-system disease. In light of the significant role circadian rhythm can hold over the body's normal physiology as well as disease processes, we examined and discussed the impact circadian rhythm and clock genes hold over lifespan, neurodegenerative disorders, and tumorigenesis. In experimental models, lifespan is significantly reduced with the introduction of arrhythmic mutants and leads to an increase in oxidative stress exposure. Interestingly, patients with Alzheimer's disease and Parkinson's disease may suffer disease onset or progression as a result of alterations in the DNA methylation of clock genes as well as prolonged pharmacological treatment for these disorders that may lead to impairment of circadian rhythm function. Tumorigenesis also can occur with the loss of a maintained circadian rhythm and lead to an increased risk for nasopharyngeal carcinoma, breast cancer, and metastatic colorectal cancer. Interestingly, the circadian clock system relies upon the regulation of the critical pathways of autophagy, the mechanistic target of rapamycin (mTOR), AMP activated protein kinase (AMPK), and silent mating type information regulation 2 homolog 1 (Saccharomyces cerevisiae) (SIRT1) as well as proliferative mechanisms that involve the wingless pathway of Wnt/β-catenin pathway to foster cell survival during injury and block tumor cell growth. Future targeting of the pathways of autophagy, mTOR, SIRT1, and Wnt that control mammalian circadian rhythm may hold the key for the development of novel and effective therapies against aging- related disorders, neurodegenerative disease, and tumorigenesis.